An evolutionary game analysis of supervision behavior in public-private partnership projects: Insights from prospect theory and mental accounting - Cheng, Xiaotong; Cheng, Min (Frontiers in Psychology, 2023)
Effective supervision is one of the important ways to ensure the smooth implementation of Public-Private Partnership (PPP) projects. To understand the characteristics of the decision-making behavior of the public and private sectors in the supervision of PPP projects and the influencing mechanisms of some factors, we combine prospect theory and mental accounting theory into the evolutionary game analysis. First, we use prospect theory to reflect the behavioral characteristics of game players when making decisions and classify the value function into a valence account and a cost account according to the mental accounting theory. Accordingly, we construct a payoff matrix based on prospect theory and mental accounting theory, and the system’s equilibrium state is analyzed. Then, based on numerical simulations, the influence of different parameters on the behavior of the public and private sectors is analyzed, and management suggestions for practical reference are put forward based on the simulation results. The results show that the greater the perceived cost of active behavior for the public and private sectors, the less likely they will take active behavior. Secondly, there is insufficient incentive for the private sector to fulfill contracts when the penalties for its opportunistic behavior are minor. Thirdly, increasing the cost reference points and decreasing the valence reference points will promote the public and private sectors to adopt active behavior. Fourth, the public sector and the private sector are more inclined to take active behavior when they need to bear more significant risk losses. This study provides new ideas for the analysis of the game players’ decision-making behaviors in the supervision of PPP projects and delivers a decision-making reference for reasonable supervision.